2020
DOI: 10.1002/app.50219
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of flame retardancy and mechanical properties of APP/EG/TPU multilayer composites prepared by microlayer coextrusion technology

Abstract: In this paper, ammonium polyphosphate(APP)/expandable graphite(EG)/thermoplastic polyurethane (TPU) composites were prepared by microlayer coextrusion technology, APP and EG fillers had good synergistic flame retardancy and excellent dispersion in TPU matrix, which greatly improved the flame retardancy and mechanical properties of multilayer composites. The dispersion of APP and EG in TPU was characterized by using SEM, the flame retardancy of composites was characterized by using UL94 and LOI, the thermal sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The results showed that the tensile strength (T s ) of pure TPU was 28.9 ± 2.3 MPa, and elongation at break (E b ) was 1310 ± 42%. The introduction of APP significantly reduced the T s and E b of TPU composites, which may be due to the stress concentration caused by the accumulation of APP in the TPU matrix, making the composites prone to cracks [ 30 ]. Furthermore, compared with TPU/5%APP, the T s and E b of TPU/5%APP-Cu increased by 25% and 12%, and the T s and E b of TPU/5%APP-Cu@PDA increased by 43% and 37%.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the tensile strength (T s ) of pure TPU was 28.9 ± 2.3 MPa, and elongation at break (E b ) was 1310 ± 42%. The introduction of APP significantly reduced the T s and E b of TPU composites, which may be due to the stress concentration caused by the accumulation of APP in the TPU matrix, making the composites prone to cracks [ 30 ]. Furthermore, compared with TPU/5%APP, the T s and E b of TPU/5%APP-Cu increased by 25% and 12%, and the T s and E b of TPU/5%APP-Cu@PDA increased by 43% and 37%.…”
Section: Resultsmentioning
confidence: 99%
“…However, the charred layer formed during combustion is very loose and easily falls off due to the “popcorn effect”. Thus, a number of investigations are focused on cooperative effects of EG with other additives to overcome this disadvantage [ 226 ], such as APP [ 227 , 228 , 229 ], MH [ 230 , 231 ], and LDH [ 232 , 233 ].…”
Section: Intumescent Flame Retardantsmentioning
confidence: 99%
“…34 The chemical components of unmodified IT are given in Table 2 35 The flame retardancy of polymer materials is improved by adding metal oxides/ metal hydroxides as flame retardants or synergistic agents into the polymer matrix. [36][37][38][39][40] Figure 2 gives the FTIR spectra of IT before and after modification. The figure shows that 3411 cm À1 is the characteristic peak of -OH asymmetric stretching vibration in crystal water.…”
Section: Characterization Of Modified Iron Tailings (Its)mentioning
confidence: 99%